Analisis Keterlibatan Dosen dalam Program Tabungan Haji Berbasis Potongan Gaji di Bank Syariah Indonesia - Ilmiyah, Izzatul (Journal of Islamic Finance and Syariah Banking, 2025)
This study aims to analyze the involvement of lecturers in the salary-deduction-based hajj savings program at Bank Syariah Indonesia (BSI), with a case study at the Islamic College (STAI) Senori Tuban. This program is designed to help employees, especially lecturers, in planning the hajj pilgrimage through an automatic monthly salary deduction scheme. This study uses a qualitative approach with a case study method, where data is obtained through in-depth interviews, direct observation, and relevant documentation. The research subjects consisted of lecturers who participated in the program, lecturers who had not participated in the program, and campus officials involved in financial administration. The results of the study indicate that the level of lecturer involvement in this program is still relatively low. The main driving factors for lecturer involvement are religious motivation and the ease of the autodebit system which makes it easy for them to save in a disciplined manner without having to make manual deposits. However, there are a number of inhibiting factors, such as financial limitations faced by most lecturers, especially those with contract or honorary status, and low sharia financial literacy which causes a lack of understanding of the contract mechanism in the hajj savings program. This study recommends strategies to increase participation through incentives, socialization and education of Islamic finance, and flexibility in determining the amount of salary deductions. Thus, it is expected that lecturers' participation in this program can increase, along with strengthening Islamic financial planning in the Islamic education environment. These findings can also be a reference for other institutions in implementing similar programs to support the spiritual and economic welfare of educators